RISK MANAGEMENT OF MOBILE CHANNEL IN TRAVEL INDUSTRY - Wei Su, Huang (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2016)
Mobile channel, like Uber or Airbnb, may lead to both cost-efficiency and flexibility, but it also inevitably triggers a certain degree of cost exposure. Unfortunately, there is little objective, scientific research focused on evaluating the risks that result from information exchange among mobile channels. In this study, the Grey Relational Analysis (GRA) were employed to identify and evaluate the risks of mobile channel business. This research finds Jurisdiction agreement and contract, and Social engineeringare the top three risk management factors. Especially in Taiwan, the law issue is the biggest rock on the road now. Collaborative consumption is a new inevitable business model, how to govern and constitute a legal environment is an unavoidable responsibility to our legislators.